Linguistic and Didactic Adapttion of Educational Mecal Texts for Foreign Students - A. V. Petrukhina (Научный диалог, 2022)
The principles of selecting educational texts of a medical profile for practical classes in Russian as a foreign language are considered. The ways of their linguodidactic adaptation for foreign students who speak Russian in the volume of the basic and first certification levels are described. The novelty of the research lies in the application of the methodology of corpus linguistics and the modeling method in the preparation of educational material for the lesson. The author presents examples of adaptation of the educational text in the discipline “Anatomy” in order to prepare students for further study of the subject and successful communication in this subject area. It has been determined that for foreign students with a basic level of Russian language proficiency, it is necessary to apply non-linguistic and linguistic adaptation of the text, while for students with a B1 language proficiency level, non-linguistic text adaptation should be carried out, aimed at preserving the meaning of the original text of the textbook. It has been established that the Latin version of the terms makes it difficult to perceive the Russian-language text and, therefore, necessitates the creation of a terminological dictionary on the subject with parallel translation into Russian and English.